Meningkatkan Repurchase Intention Dimoderasi Sales Promotion (Studi pada Penjualan DRW Skincare di Danesha Beauty Klinik Kota Serang) - Kartikasari, Devini; Muetia, Muetia; Lutfi, Lutfi (Sahabat Publikasi, 2025)
In an increasingly competitive skincare industry, repurchase intention is a critical factor to retain customers. DRW Skincare as a local brand faces challenges in building customer loyalty, while the role of customer experience, influencer credibility, and sales promotion has not been fully optimized. This research was conducted with the aim of developing a basic theoretical model and a new empirical research model to solve the gap in previous research results regarding the role of customer experience and influencer credibility on repurchase intention through sales promotion. This study uses descriptive and explanatory quantitative methods. The population in this study is the people of Serang city who have purchased DRW Skincare products at Danesha Beauty Clinic. The sampling technique in this study was nonprobability sampling using the purposive sampling method with a sample of 200 respondents. The data analysis technique used Partial Least Square (PLS) using Smart PLS 4.1.0.9 software. The results of the study are known: 1) customer experience has a positive and significant effect on repurchse intention. 2) influencers have a positive but not significant effect, 3) sales promotion has a positive and significant effect on repurchase intention, 4) sales promotion does not moderate influencer credibility on repurchase intention, 5) sales promotion does not moderate customer experience on repurchase intention. Marketing strategies need to focus on improving customer experience and utilizing credible influencers, while sales promotion needs to be redesigned to play an effective moderator role.